Trend of Public Mass Transport Indicators – As a Tool of Transport Management and Development of Regions - Jana Dicova; Jan Ondrus (Communications - Scientific letters of the University of Zilina, 2010)
Quantification of customer requirements is necessary for all managers that continually monitor changing transport market environment and the quantification also introduces a fundamental tool that allows evaluations of current situation. On the basic assess of reached results in last periods of time the quantification also contributes to create a quality proposal of future lead to entrepreneurship in transport. The article deals with problems of possible application of appropriate methods of application that allow to reach the best quantification of next customer requirements in transport, also contribute to realization of strategic objectives and development and improve decision making concerning next trends in region.